Carer perspectives of factors affecting placement trajectories of children in out-of-home care. (June 2016) - Withington, Tania; Burton, Judith; Lonne, Bob; Eviers, Areana
Abstract: Carers are at the frontline working with children in the care of the child protection system. This paper reports carer's views about key factors influencing the placement trajectories of children and young people living in out-of-home care in Queensland, Australia. The study sample included 21 foster and kinship carers with a minimum two-year experience in the carer role. Study data were from semi-structured telephone interviews in which carers shared their experiences of the factors impacting upon placement stability and placement movement. Carers' responses were analysed thematically. Data analysis yielded an overarching theme regarding placement trajectory: Carer engagement, and its three sub-themes; with the child; with the child protection system; and, with the caring role. Findings suggested that carer engagement and 'fit' are complex constructs that play critical influential roles in placement outcomes (stability or movement) for individual children in out-of-home care. It is argued that practice needs to be better grounded in these relational dynamics, and better aligned concerning the power differentials that exist. Highlights: Carers report that the engagement of carers across the child protection system is a critical factor in building and maintaining stable placements for children and young people living in out-of-home care Carers' perspectives indicate that shifts in child protection services culture, practice and policy is required to integrate the importance of the relational aspect of out-of-home care in placement outcomes Carer engagement is a complex construct with implications for the placement trajectory of children in out-of-home care.